Impact of T1 Slope Visibility on Cervical Sagittal Alignment: A Comparative Study of Radiographic Parameters According to T1 Slope Visibility - Hiroaki Nakashima; Akiyuki Matsumoto; Sadayuki Ito; Naoki Segi; Jun Ouchida; Ippei Yamauchi; Yoshinori Morita; Shiro Imagama (Spine Surgery and Related Research)
Introduction: Proper cervical sagittal alignment is essential for maintaining overall spinal stability and function. A crucial measure of this alignment is the T1 slope, which is an important indicator. However, lateral cervical spine radiographs often fail to clearly show the T1 slope owing to several factors, such as shoulder anatomy or variations in body shape. In this study, we aimed to evaluate the differences in cervical alignment between individuals with visible and invisible T1 slopes. Methods: This study was a retrospective cohort analysis involving 60 patients diagnosed with cervical spine conditions and evaluated via radiographic imaging. The patients were categorized into two groups based on whether the T1 slope was clearly visible or not. Key radiographic measurements, such as the C2-C7 sagittal vertical axis (SVA) and C2-C7 Cobb angles in the neutral, flexion, and extension postures, were recorded and statistically analyzed. Results: Significant differences were observed in the C2-C7 SVA between the groups, particularly among men. Men in the invisible T1 slope group had an average SVA of 28.9 mm, whereas those in the visible group had a mean SVA of 16.0 mm (P<0.05). Although no notable differences were observed in the Cobb angles for the neutral and flexion positions, a substantial reduction in the extension Cobb angle was noted in the invisible than in the visible group (24.4° vs. 37.6°, P<0.05). Conclusions: Male patients with obscured T1 slopes exhibited unique radiographic features, including higher C2-C7 SVA and diminished extension capacity. This suggests that the visibility of the T1 slope plays a pivotal role in the evaluation of cervical alignment. Furthermore, the exclusion of patients with an invisible T1 slope from research studies could lead to biased results.